Westerly drives long-distance transport of radionuclides from nuclear events to glaciers in the Third Pole. (December 2022) - Deji,; Yao, Tandong; Thompson, Lonnie G.; Davis, Mary E.; Xu, Baiqing; Wu, Guangjian; Liang, Sujie; Zhao, Huabiao; Zhu, Meilin; You, Chao
Abstract: Major nuclear bomb tests and nuclear power plant incidents release large amounts of radionuclides. This study investigates beta (β) activities of radionuclides from four ice cores in the Third Pole (TP) to understand the transport routes and related atmospheric processes affecting the radionuclides deposition in glaciers of the region. All the ice cores show three major β activity peaks in the ice layers corresponding to 1963, 1986, and 2011. The β activity peak in the 1963 ice layer is referred to as the well-known 1962 Nuclear Bomb Test. Beta activity peaks in 1986 and 2011 ice layers from the Chernobyl and Fukushima Nuclear Incidents (CNI, FNI). Hysplit forward and backward trajectory analyses suggest that the radionuclides were transported by the westerly into the stratosphere and then to the high elevation TP glaciers. In the FNI case, the radionuclides traveled over Japan, the Pacific Ocean, Europe, and central Asia before being deposited in the TP glaciers. Investigations of the atmospheric circulation confirm that the stronger northern branch of westerly is responsible for high radionuclides during the FNI in the TP. Less precipitation with water vapor flux component divergence after the FNI also contributed to the enriched radionuclides. Highlights: We report 3 nuclear events, FNI, CNI, and NBT from β activity peak in TP ice cores. We found more radionuclides in ice core records after FNI than that after CNI. Atmosphere transports are responsible for the difference between FNI and CNI. Strong northern westerly after FNI is responsible for more radionuclides. Less precipitation and water vapor divergence after FNI led to more radionuclides.